1990
DOI: 10.1093/jn/120.8.876
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Calcium Citrate-Malate on Skeletal Development in Young, Growing Rats

Abstract: It has been previously demonstrated that calcium from calcium citrate-malate (CCM), a mixture of calcium, citric acid and malic acid, is better-absorbed than calcium from calcium carbonate (CaCO3) in humans and in rats. It was of interest to determine if this differential in absorption would result in differences in bone development under chronic feeding conditions. The present study was designed to compare CCM with CaCO3 for effects on bone development in weanling female C/D rats fed either CCM or CaCO3 at 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

1995
1995
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 12 publications
1
5
0
Order By: Relevance
“…Citrate, acetate and lactate were superior to the inorganic Ca sources, especially with respect to true absorption. A similar ranking is known also from other divalent kations (W eigand and K irchgessner 1979; R oth and K irchgessner 1983; K ochanowski 1990). One major reason for the superior absorptive potential of organic compounds may be their high solubility in the digestive tract and in part also their propensity to formulate chelates.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Citrate, acetate and lactate were superior to the inorganic Ca sources, especially with respect to true absorption. A similar ranking is known also from other divalent kations (W eigand and K irchgessner 1979; R oth and K irchgessner 1983; K ochanowski 1990). One major reason for the superior absorptive potential of organic compounds may be their high solubility in the digestive tract and in part also their propensity to formulate chelates.…”
Section: Discussionsupporting
confidence: 66%
“…This potential is usually addressed by the term ‘bioavailability’. Most attempts to estimate Ca bioavailability are based on in vitro methods such as solubility and dialysability or indirect in vivo parameters such as bone characteristics (K ochanowski 1990; S hen et al 1995; T rinidad et al 1996). Indeed, these methods may detect relative graduations among dietary Ca sources but they do not provide quantitative figures of bioavailability.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it has been reported that calcium-citrate-malate (CCM), a mixture of Ca carbonate, citric acid, and malic acid, exhibits approximately six times the solubility of either Ca citrate or Ca malate, both of which are much more soluble in water than Ca carbonate is (17). It is also well known that Ca from CCM is better absorbed in humans and animals than Ca from Ca carbonate is (18)(19)(20)(21). Similar to CCM, TBE is a composite salt of Ca phosphate derived from bovine bone, citric acid, and malic acid.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of calcium supplementation on skeletal development in four groups of 14 C/D female rats administered for 4 or 12 weeks as calcium citrate malate, measured as cortical and trabecular 2 bone formation, was compared with administration of CaCO 3 (Kochanowski, 1990). Animals fed calcium citrate malate showed significantly more trabecular bone formation after 4 weeks (44 to 47% more) and 12 weeks of treatment (23-25% more) than rats fed CaCO 3 .…”
Section: Bioavailability Of Calcium From the Sourcementioning
confidence: 99%